2015
DOI: 10.1515/bvip-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Galanin - Immunoreactive Nerve Fibers in the Mucosal Layer of the Canine Gastrointestinal Tract During Inflammatory Bowel Disease

Abstract: The effect of inflammatory bowel disease (IBD) on the density of galanin -immunoreactive (GAL-IR) nerve fibers was determined in the mucosa of canine duodenum, jejunum, and descending colon. Fiber density was evaluated by a single immunofluorescence method in biopsy specimens obtained from healthy dogs and patients with variable severity of the disease. The density of GAL-IR nerve fibers was determined by the semi-quantitative method by counting fibers in the field of view (0.l mm 2 ). Fiber density was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Galanin exhibits neuroprotective properties and acts as an inhibitory neuromodulator [ 46 ]. An increase in GAL activity has been noted in pigs after long-term supplementation with a non-steroidal anti-inflammatory drug [ 33 ] acrylamide [ 109 ] or in dogs with IBD [ 31 ]. Galanin may affect the motility of the gastrointestinal tract by inhibiting acetylcholine and SP via excitatory GAL-R 1 receptors [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galanin exhibits neuroprotective properties and acts as an inhibitory neuromodulator [ 46 ]. An increase in GAL activity has been noted in pigs after long-term supplementation with a non-steroidal anti-inflammatory drug [ 33 ] acrylamide [ 109 ] or in dogs with IBD [ 31 ]. Galanin may affect the motility of the gastrointestinal tract by inhibiting acetylcholine and SP via excitatory GAL-R 1 receptors [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of ganglia and nerve fibers lying in the wall of the esophagus, stomach, small and large intestines, pancreas, bile ducts and gallbladder [ 22 ]. The change in neurotransmitter coding is influenced by a number of factors, including age [ 23 , 24 ], intestinal microbiota [ 25 , 26 ], pathological conditions such as diabetes [ 27 , 28 ] or inflammatory bowel disease (IBD) [ 29 31 ], substances which we take more or less consciously, such as non-steroidal anti-inflammatory drugs [ 32 , 33 ] and bisphenols [ 34 ]. In pigs, which are a model organism in human biomedical research and whose anatomical structure resembles the human anatomical structure in the intestines [ 35 38 ] we can distinguish three plexuses: myenteric (MP) and submucous, which is further subdivided into the outer (OSP) and inner (ISP) submucous plexus [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms are accompanied by histopathological changes in the small intestine and/or the colon. Recent studies have shown that substances acting as neurotransmitters and/or neuromodulators in the enteric nervous system (ENS) and extrinsic innervation of the gastrointestinal tract could be implicated in the pathogenesis of intestinal inflammations [ 6 , 7 , 8 ]. However, the exact roles of the majority of active neuronal substances in the pathophysiology of IBD have not been yet elucidated.…”
Section: Introductionmentioning
confidence: 99%